I protein: bacteriophage T7-coded inhibitor of Escherichia coli RNA polymerase. - Hesselbach, B A (1977)
Bacteriophage T7-coded inhibitor of Escherichia coli RNA polymerase, termed I protein, was purified from an inactive E. coli RNA polymerase-I protein complex isolated from phage T7-infected cells. A molecular weight of about 7,000 to 9,000 was assigned to the purified I protein by acrylamide-sodium dodecyl sulfate gel electrophoresis, Sephadex G-50 gel filtration, and glycerol gradient centrifugation analysis. I protein inhibits initiation of RNA synthesis by directly binding to the RNA polymerase holoenzyme and prevents the binding of the enzyme to the promoter sites on the template T7 DNA. However, once a highly stable transcriptional preinitiation complex between RNA polymerase holoenzyme and T7 DNA is formed at the promoter site on T7 DNA in the absence of nucleoside triphosphates, I protein does not inhibit the initiation of RNA synthesis by this preformed complex upon addition of nucleoside triphosphates. RNA synthesis by the core RNA polymerase and the binding of core RNA polymerase with template DNA are not inhibited by I protein, although a partial association between the core enzyme and I protein can be observed. I protein does not bind to sigma factor or T7 DNA. Therefore, binding of I protein with the RNA polymerase, which results in the inhibition of initiation of RNA synthesis, requires the presence of sigma factor in the RNA polymerase holoenzyme form.